Analisis Peranan Action Dalam Memudahkan Nasabah Untuk Melakukan Transaksi Pada Pt Bank Aceh Syariah Cabang Kutacane - Nurhapirah Tasnim; Nurbaiti Nurbaiti (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
This study aims to determine how satisfied people are in using the Action Link application which is a mobile banking owned by Bank Aceh Syariah. The growth of technology that continues to increase from year to year so that this can have an impact on society. Technology has developed rapidly and is increasingly modern, many companies are developing performance in the information sector so that people are adopted in using online services via smartphones such as the Action service (Aceh Online Transaction) at Bank Aceh Syariah. This study uses descriptive analysis as a research approach that uses qualitative research. The technique used in this study is to conduct interviews with customers and distribute questionnaires to users of the Action application. The results of the study show that M-Banking Action makes it very easy for customers to make transactions, but there are some shortcomings in the application because there are no complete features. The quality of service also certainly has an impact on customer perceptions in using the application so that customers are still less confident in using Action if the service provided is bad and there are still those who feel less safe in using it.